2002
DOI: 10.1081/lpr-120004784
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-Enabled Synergistic Interaction of Antimicrobial Agents

Abstract: Antimicrobial agents may interact synergistically when both drugs are present at the infected site for an adequate period of time at sufficient concentrations. Generally speaking, the agents in the combination show different tissue distributions and pharmacokinetics. By co-encapsulation of the drugs in a drug carrier, like liposomes, parallel tissue distributions of both drugs may be ensured and drug concentrations at the site of infection may be increased. In this presentation therapeutic efficacy of liposome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…It is very likely that the success of liposome chemotherapy is due to this passive targeting; however, targeting is not specific to liposomes, but should be common to all nanoparticle drug delivery schemes. Passive targeting also has been observed in infectious or inflammatory pathologies, as substantial liposome localization at the target site has been demonstrated in a variety of models of infection and inflammation [14]. Long-circulation times have been shown to be linearly related to the degree of target localization in inflammation as well [14].…”
Section: Targetingmentioning
confidence: 97%
See 2 more Smart Citations
“…It is very likely that the success of liposome chemotherapy is due to this passive targeting; however, targeting is not specific to liposomes, but should be common to all nanoparticle drug delivery schemes. Passive targeting also has been observed in infectious or inflammatory pathologies, as substantial liposome localization at the target site has been demonstrated in a variety of models of infection and inflammation [14]. Long-circulation times have been shown to be linearly related to the degree of target localization in inflammation as well [14].…”
Section: Targetingmentioning
confidence: 97%
“…Both biocompatibility and stability can be imparted on colloidal particles or emulsion droplets by encapsulation within a bilayer membrane; changes in ionic environment that would lead to flocculation would be interrupted by the bilayer, and the size of the flocs would be limited, minimizing sedimentation. The vesosome structure could be used to deliver a cocktail of antibiotics or antimicrobials to sites at a fixed ratio; such mixtures have been shown to act synergistically when delivered in a single liposome [14]. Such multi-drug formulations may be useful to avoid inducing pathogen resistance to a single drug.…”
Section: New Structures -Multiple Membranes For Multiple Tasks and Mumentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is limited data on coencapsulation of two different drugs in one liposomal formulation 39. Gentamicin and ceftazidime have been coencapsulated into liposomes and the in vivo synergistic effect has been demonstrated by a rat model of pneumonia 40–42. In another study, isoniazid and rifampicin were successfully coencapsulated into liposomes, but no study of beneficial effect was presented 43–45.…”
Section: Introductionmentioning
confidence: 99%
“…39 Gentamicin and ceftazidime have been coencapsulated into liposomes and the in vivo synergistic effect has been demonstrated by a rat model of pneumonia. [40][41][42] In another study, isoniazid and rifampicin were successfully coencapsulated into liposomes, but no study of beneficial effect was presented. [43][44][45] To date, no studies have coencapsulated FLU/MTO nor demonstrated therapeutic benefit of such a combination.…”
Section: Introductionmentioning
confidence: 99%